Execution of Recognition of Grosse Documents Made Payable Notary - Rekowarno Rekowarno (Jurnal Daulat Hukum, 2018)
This study, entitled: Implementation of Execution of Deed of Acknowledgment of Debt Groose Created Notary, the problems of this study are 1) How is the execution of the Deed of Acknowledgment of Debt Groose made Notary? 2) What are the barriers and solutions in the execution of the Deed of Acknowledgment of Debt Groose made Notary? The method used in this research using normative juridical approach, which includes research principles of law, the legal systematics, synchronization of law, legal history and comparative law. The results using this method Sociological Juridical conclude that: 1) Execution of a debt recognition grosse deed as authentic deeds in the lending agreement, can only be carried out under the leadership of Chairman of the Court (court fiat) local. Not that grosse deed of acknowledgment of debt which includes the phrase, "As Justice Based on God" the legal force equivalent Court decision that has binding can be carried out executions without trial fiat (parate execution). Precisely because equated with court decisions that have permanent legal force, the implementation of the execution must be at the behest and under the leadership of Chairman of the Court, 2)Barriers execution grosse deed of acknowledgment of debt arose because of noncompliance with formal requirements, the form must be as specified by the Act and the terms of material, which is the amount of debt must be certain or uncertain, the deed must be an acknowledgment of debt unilaterally from the debtor, and not to be confounded with the grosse deed mortgages. These problems can result grosse deed recognition execution request Debt can not be accepted by the President of the Court State and cause grosse deed of recognition The debt does not have the power executorial,Keywords: Execution Groose, Deed of Acknowledgment of Debt, Notary.